(untitled) (Innovate Conferences, 2025)
This thesis examines methods to improve the strike reaction speed of sambo athletes as they prepare for hand-to-hand combat competitions. “Strike reaction” refers to the ability to quickly respond to an opponent’s attack or to initiate a rapid counter-strike – a critical skill in both sport and combat settings. Through a review of sports science literature and training methodologies, the thesis explores the components of reaction time (simple and choice reaction), the role of anticipation and reflexes, and drills or technologies that can enhance reaction speed. Key findings indicate that elite combat athletes typically have significantly faster reaction times than novices due to superior perceptual anticipation and neural adaptation. Training interventions such as specialized reaction drills, neuromuscular electrical stimulation, and sensory focus techniques can yield measurable improvements in reaction speed (e.g., reductions in response latency by 9% after targeted training). The thesis discusses practical exercises – from partner drills that train fighters to read pre-attack cues to modern reaction light systems – and underscores the importance of reducing the latency of response (the time between seeing a stimulus and initiating movement). Additionally, it addresses the need to train decision reaction time (choosing the correct response among options) since hand-to-hand combat often involves complex stimuli. The discussion includes how psychological factors like staying relaxed under pressure and not “freezing” contribute to faster reactions, as well as how consistent training can override natural startle responses (e.g., flinching). Concluding, the thesis provides evidence-based recommendations for coaches to incorporate reaction enhancement protocols in sambo training, ultimately improving athletes’ readiness and performance in hand-to-hand combat events.